Assessing mental health literacy among patients with chronic physical diseases and its associated sociodemographic factors - Le, Tran Tuan Anh; Tran, Nhu Minh Hang; Ho, Dung; Tran, Huu Vinh; Lam, Tu Bao; Nguyen, Thi Hong Ngat; Pham, Minh Tuan; Nguyen, Van Tri; Ngo, Thi Kim Cuc (Tạp chí Y Dược Huế, 2025)
Background: Mental health literacy (MHL) remains insufficiently addressed in Vietnam, especially among individuals with chronic diseases, who face increased vulnerability to mental health problems. This study examines MHL levels among patients with chronic physical diseases and explores the associated sociodemographic factors, aiming to inform targeted interventions for enhanced mental health care. Methods: A cross-sectional study was conducted with 200 adult inpatients at Hue University of Medicine and Pharmacy Hospital from August to December 2023. The Vietnamese version of the Mental Health Knowledge Questionnaire (MHKQ) was used to measure MHL. Univariate logistic regression was used to identify factors associated with lower MHKQ scores. Factors with a p-value <0.05 in univariate analysis were included in a multivariate logistic regression model. Results: The mean MHKQ score was 7.7, indicating limited MHL, with prevalent misconceptions about mental disorders and low awareness of mental health days. Multivariate analyses highlighted significant associations with lower MHL among those with primary education (OR: 20.23). However, rural residents (OR: 5.35) were more likely to have lower MHKQ score compared with urban residents. Conclusion: The study reveals low MHL among pariticipants, influenced by sociodemographic factors like rural residency and education level. These findings suggest the need for targeted mental health education, especially for rural and low-education populations, to improve comprehensive care and mental health outcomes for patients with chronic conditions in Vietnam.